NLRP3 inflammasome-induced pyroptosis in digestive system tumors - Wen, Jiexia; Xuan, Bin; Liu, Yang; Wang, Liwei; He, Li; Meng, Xiangcai; Zhou, Tao; Wang, Yimin (Frontiers in Immunology, 2023)
Programmed cell death (PCD) refers to cell death in a manner that depends on specific genes encoding signals or activities. PCD includes apoptosis, pyroptosis, autophagy and necrosis (programmed necrosis). Among these mechanisms, pyroptosis is mediated by the gasdermin family and is accompanied by inflammatory and immune responses. When pathogens or other danger signals are detected, cytokine action and inflammasomes (cytoplasmic multiprotein complexes) lead to pyroptosis. The relationship between pyroptosis and cancer is complex and the effect of pyroptosis on cancer varies in different tissue and genetic backgrounds. On the one hand, pyroptosis can inhibit tumorigenesis and progression; on the other hand, pyroptosis, as a pro-inflammatory death, can promote tumor growth by creating a microenvironment suitable for tumor cell growth. Indeed, the NLRP3 inflammasome is known to mediate pyroptosis in digestive system tumors, such as gastric cancer, pancreatic ductal adenocarcinoma, gallbladder cancer, oral squamous cell carcinoma, esophageal squamous cell carcinoma, in which a pyroptosis-induced cellular inflammatory response inhibits tumor development. The same process occurs in hepatocellular carcinoma and some colorectal cancers. The current review summarizes mechanisms and pathways of pyroptosis, outlining the involvement of NLRP3 inflammasome-mediated pyroptosis in digestive system tumors.